Model Kepemimpinan Kyai dalam Membentuk Santri Mandiri Di Era 4.0 - Imam Safi`i (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
The research aimed to ; 1) describe and analyse how the leadership type of Kyai Mohammad Ali Shobirin in forming independent santri; 2). what kind of habits were done in the Islamic dorm of al Qoyyim , to form independent santri; 3). model of Kyai Ali shobirin leadership in forming independent santri in the islamic dorm Al Qoyyim Kasembon Malang. The applied research method to answer the aim above was grounded theory, because the research was field research. While the references consisted of primary, secondary and tertiary data. Collecting data by observation, interviews and documentation. Data analyze used qualitattive data analyze. The research showed that kyai Ali Shobirin belonged to the one of three type of leadership. Firstly, visionary leadership. Secondly, transformative leadership. Thirdly, charismatic leadership. The habit of Santri to form independent santri in the era 4.0 was discipline in every aspect, santri ‘s habituality to be entrepeneur and The model of leadership of kyai Ali Shobirin was individual-kolektif, it happened because collaboration in developing Islamic dorm. While, the policy was taken by the head dominantly.